Argentina - Small and Medium-Sized Enterprises in Argentina : A Potential Engine for Economic Growth and Employment - World Bank (Washington, DC, 2013)
The convertibility law, and economic liberalization in the early 1990s in Argentina, brought about dramatic changes in economic performance. To adjust to increasing globalization, and a series of external shocks, small and medium size enterprises (SMEs) were confronted with the task of developing business strategies to secure their niches in the new arena. However, such strategies were obstructed by constraints in the legal, and economic framework, weak information and technology aspects, and insufficient access to finance. The report builds on the following issues: 1) the critical aspect of the SME sector to the Argentine economy, both from a growth/efficiency, and equity standpoint; yet on average, SMEs have failed to attain their potential; 2) the highly heterogeneous configuration, particular organizational, and technological characteristics of SMEs; 3) the high degree of institutional rigidity of the country's business environment; 4) the need to develop policy actions to deepen financial markets for SMEs; 5) the significant knowledge constraints - by and large, no training nor technical assistance services are available, mainly because of high costs; 6) the striking multiplicity of SME programs, yet with uncertain impact; and, 7) the need to overhaul SME policies, and programs to prod more incentive- and demand-driven approaches. Elements for effective SMEs assistance programs include the development of a standard set of metrics to measure performance of SMEs, and, entrepreneurial management, deemed of critical importance. As well, cost recovery growth should be targeted, extensively using follow-up techniques, and leveraging their effectiveness through the use of information, and communications technology. Most importantly, the policy challenge lies in taking initiatives to develop institutions at the national, and local levels, to encourage transition from inward-looking firms, narrow search routines, and information-poor markets, to learning-oriented firms, and mature, information-rich markets.